(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
This study aimed to demonstrate the impact of financial and operational risks on the profitability of Iraqi Islamic banks as of (2014-2019), where the study population consists of all employees of Iraqi Islamic banks, with a total of (8) banks. The sample of the study consisted of (50) individuals. Eviews software was used for statistical analysis, and the analytical descriptive statistical method was applied in this study. To achieve the study objectives, the following indicators were used to express financial risks: credit risk, interest rate risk, liquidity risk, and capital adequacy risk. The indicators below were used to express: With regard to financial performance (return on assets, return on equity), the difficulty of the research was the significant growth in these risks due to technological progress and the creation of new financial instruments, and the study found that financial risks had a harmful effect On the financial performance of the Iraqi banks. In the light of the previous results. The report concluded with a number of suggestions, the most important of which are: the need for Iraqi banks to implement a specific plan for risk management that improves financial performance, as well as setting up preventive and corrective internal control mechanisms. Credit grants are expanded.